Comparative adsorption isotherm for beryllium oxide/ iron (Iii) oxide toward co2 adsorption and desorption studies - Lahuri A.H.; Yarmo M.A.; Abu Tahari M.N.; Marliza T.S.; Tengku Saharuddin T.S.; Wun Fui M.L.; Dzakaria N. (Trans Tech Publications Ltd, 2024)
Indexed by Scopus/ERA/MyCite